2000
DOI: 10.1128/jvi.74.20.9617-9628.2000
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adenovirus Induces Maturation of Dendritic Cells via an NF-κB-Dependent Pathway

Abstract: Recombinant adenovirus (rAd) infection is one of the most effective and frequently employed methods to transduce dendritic cells (DC).Contradictory results have been reported recently concerning the influence of rAd on the differentiation and activation of DC. In this report, we show that, as a result of rAd infection, mouse bone marrow-derived immature DC upregulate expression of major histocompatibility complex class I and II antigens, costimulatory molecules (CD40, CD80, and CD86), and the adhesion molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
169
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(199 citation statements)
references
References 68 publications
26
169
4
Order By: Relevance
“…This conjecture is supported by several reports that demonstrated the promotion of DC maturation by Ad infection. [51][52][53] In particular, Morelli et al 54 reported that Ad-infected DCs matured via a NFkB-dependent pathway, regardless of transgenic sequences or Ad-genome transcription. However, Dietz et al 55 demonstrated that the expression of CD83 and IL-12 p40 was unaffected by Ad infection or transferred gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This conjecture is supported by several reports that demonstrated the promotion of DC maturation by Ad infection. [51][52][53] In particular, Morelli et al 54 reported that Ad-infected DCs matured via a NFkB-dependent pathway, regardless of transgenic sequences or Ad-genome transcription. However, Dietz et al 55 demonstrated that the expression of CD83 and IL-12 p40 was unaffected by Ad infection or transferred gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recombinant adenoviral vectors have been shown to activate NF-kB in murine hepatocytes, murine dendritic cells and human vascular smooth muscle cells. [8][9][10] These reports suggested a role for NFkB in the transcriptional regulation of ICAM-1 gene induced by Ad.CFTR. Inactive NF-kB/Rel proteins are located in the cytoplasm as heterodimers and homodimers which are bound to inhibitory proteins termed IkBs.…”
Section: Moter Adcftr Also Stimulated a 13-fold Increase In Nfkb-dementioning
confidence: 99%
“…Using results of the group of DC or fibroblasts transfected with IL-12, they were found to be statistically different (p Ͻ 0.05) than the other groups using Mann-Whitney's U-test. At this point it is worth mentioning that we and others have previously reported moderate changes in surface molecules towards maturation in adenovirally transfected DC [41,42].…”
Section: Human Immature Monocyte-derived DC Augment Nk Activities Inmentioning
confidence: 87%